Non-smooth dynamics and multiple equilibria in a Cournt-Ramsey model with endogenous markups - Brito, Paulo (2010)
We consider a Ramsey model with a continuum of Cournotian industries where free entry generates an endogenous markup. The model produces two different regimes, monopoly and oligopoly, resulting in non-smooth dynamics. We analyze the global dynamics of the model, demonstrating the model may exhibit heteroclinic orbits connecting multiple equi¬libria. Small transitory changes in parameters can lead to large permanent effects and there can be a Rostovian poverty trap separating a low-capital and high-markup equilibrium from a high-capital low-markup equilibrium. The paper applies recent results from applied math¬ematics for non-smooth dynamic systems.